2013
DOI: 10.1080/00223980.2012.717552
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Contract Types as Moderator in the Breach-Violation and Violation-Burnout Relationships

Abstract: This research examined the relationships between perceived psychological contract breach, felt violation, and burnout in a sample (n = 361) of employees from various organizations in Pakistan. The moderating role of contract types in these relationships was also tested. Findings supported a positive association between perceived psychological contract breach and felt violation and both were positively related to burnout. Transactional and relational contracts moderated the felt violation-burnout relationship. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 65 publications
1
35
0
2
Order By: Relevance
“…Furthermore, we theorized about and assessed only one moderating condition of the relationship. However, it may be that other mechanisms such as emotional exhaustion (Jamil et al, 2013) also play an important role here. However, we did not assess additional mediators or moderators in our study.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we theorized about and assessed only one moderating condition of the relationship. However, it may be that other mechanisms such as emotional exhaustion (Jamil et al, 2013) also play an important role here. However, we did not assess additional mediators or moderators in our study.…”
Section: Limitationsmentioning
confidence: 99%
“…Researchers have also shown that broken promises and feelings of betrayal trigger more intense emotional reactions that even imply a deterioration of a person's health and well‐being (Conway & Briner, ; Jamil, Raja, & Darr, ; Lapointe, Vandenberghe, & Boudrias, ; Robbins, Ford, & Tetrick, ; Kalimo, Taris, & Schaufeli, ; Penhaligon, Louis, & Restubog, ; Shani & Pizam, ; Vearing & Mak, ). For example, Conway and Briner () looked to depression as a way to assess strong negative daily moods as a response to a perceived broken contract.…”
Section: The Relationship Between Psychological Contract Violation Dmentioning
confidence: 99%
“…Numerous researchers have analysed the detrimental impact of psychological contract breach on workplace relationships (Conway and Briner (2002); Parzefall and Hakanen (2010)). When employees having positive psychological strengths perceived un-fulfilment of certain obligations or promises in their employment contract implied by their employers then this particular situation becomes the source of creating perceptions of breach among them (Coyle-Shapiro and Kessler (2000); Morrison and Robinson (1997); Restubog et al (2006); Robinson (1996); Rousseau (1995)), that ultimately leads to feelings of betrayal (Robinson (1996); Robinson and Rousseau (1994)), and that negative attitude & behaviour eventually results in disloyalty & unfaithfulness, lack of trust and commitment, poor performance, high turnover Robinson and Rousseau (1994); cut back on constructive behaviours, for example, low citizenship behaviour and in-role performance (Robinson (1996); Robinson and Morrison (1995)); as well as lower engagement and higher burnout towards their work Chambel and Oliveira-Cruz (2010).While on experiencing breach, employees see themselves in a condition of inequity & they reinstate equity by an emotionally strong response in the form of lower work engagement, Parzefall and Hakanen (2010) & higher burnout Jamil, Raja, and Darr (2013). Some researchers have revealed that contract breach threatens sense of control from their environment & that ultimately becomes source of their burnout (Gakovic and Tetrick (2003); Topa and Morales (2005)).…”
Section: H2mentioning
confidence: 99%
“…When employees operate in adverse, resource-depleting work environments, they exhibit lower work motivation and engage in fewer productive work behaviors (Coelho, Augusto, & Lages, 2011;Hobfoll & Shirom, 2000;Jamil, Raja, & Darr, 2013;Perko, Kinnunen, & Feldt, 2017). Such workplace adversity might result from the belief that an employer has broken its psychological contract with them-that is, the implicit agreement about the obligations that the employer has toward them (Rayton & Yalabik, 2014;Robinson & Rousseau, 1994;Sonnenberg, Koene, & Paauwe, 2011).…”
Section: Introductionmentioning
confidence: 99%